PENGARUH PERSEPSI SISWA TENTANG METODE MENGAJAR GURU DAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN TATA KELOLA SARANA DAN PRASARANA KELAS XI JURUSAN ADMINISTRASI PERKANTORAN SMK NEGERI 1 SUKOHARJO TAHUN AJARAN 2018/201 - Fajriati Fatimah Azzahra (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2019)
The research aims to identify effect of: (1) students perception on the teaching methods of teachers to the learning achievement of students subjects for governance and infrastructure; (2) students perception on the usability of the media learning on the learning achievement of students subjects for governance and infrastructure; (3) students perception of teacher teaching methods and the use of media learning on the learning achievement of students subjects for governance and infrastructure. The population in this study is all students of class XI office administration of SMK Negeri 1 Sukoharjo amounting to 108 student. The research was an quantitative method with style correlation. Research results: (1) Have a significant effect of students perception of the teacher's teaching method on the learning achievement of the students by the tcount 7.131> ttable 1.989 with the significantly 5%;(2) Have a significant effect of students  perception of the use of media learning on the learning achievement of students by the tcount 3.898 > ttable 1.989 with the significantly 5%; (3) Have  a significant effect of students perception of teacher teaching methods and the use of media learning to study achievement of students by the value of Fcount 59.143 > Ftable 3.11with significantly 5%.